PENANGGULANGAN KENAKALAN REMAJA DI SMP DAARUT TAUHID BOARDING SCHOOL - Herlina, Hani; Kosasih, Aceng (SOSIETAS, 2016)
This study investigates the prevention of juvenile delinquency at a boarding school, i.e. Daarut Tauhid Secondary Boarding School. The aim of this study is to explore the preventive and repressive attempts made by the boarding school to overcome juvenile delinquency. This study employed a qualitative approach in the framework of a study case method. Observation, interview, and documentation were used as the data collection. The informants of this study consisted of Darut Tauhid Boarding School staffs, the students, and the people who lived around the school area. The results of this study show that the preventive and repressive attempt to prevent juvenile delinquency is made by maximizing the role of Islamic education.